Threading Transformative Impact of Artificial Intelligence: Navigating Challenges and Opportunities in L2 Writing Among Students - Santos Jr., Remie S. Delos; Tulud, Donnie M. (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to comprehensively explore the intersection of Artificial Intelligence (AI) and second language (L2) writing education. As AI technologies rapidly advance, they are increasingly integrated into educational practices, particularly in language learning environments. Methodology: This study used a descriptive qualitative research design to explore the impact of AI on L2 writing among students at the University of Southern Mindanao. Thirty students participated, with 25 in individual interviews and 5 in a focus group discussion. Participants had used AI writing tools extensively and were enrolled in undergraduate programs with at least intermediate proficiency in English or their L2. Main Findings: The study found that students' adoption of AI in L2 writing depends on its perceived usefulness and ease of use. AI offers opportunities to enhance writing quality but also presents challenges, including negative effects on critical thinking, writing process, and confidence. Despite these challenges, students found ways to overcome them, emphasizing the need for ethical integration, originality, and independence. Novelty/Originality of this study: This study uniquely explores AI's transformative impact on second language (L2) writing, focusing on both its benefits (enhanced writing quality, personalized learning) and challenges (impacts on critical thinking, confidence, and independence).